Research on Multi-loop Cross-eye Jamming Optimization Based on Wavefront Phase Distortion. Issue 6 (February 2019) - Hongwei, Wang; Guowei, Wang; Xi, Zhang
Abstract: The strict implementation conditions of cross-eye jamming can be effective improved by multi-loop cross-eye jamming, so it has become a stirring research topic. In this paper, the characteristics of wave-front phase distortion in multi-loop cross-eye jamming system are investigated by using two indexes, the degree of center distortion(DCD) and the effective distortion region(EDR). Firstly, the synthetic field model of multi-element jamming signal is derived, and the constraint model is established by taking DCD and EDR as objective functions. Secondly, the parameters such as amplitude ratio, phase difference and the number of loops are optimized by MOEA/D algorithm. Finally, the jamming effect of radar tracking angle is verified by simulation. The results show that, compared with the single loop jamming system, multi-loop cross-eye jamming system can effectively improve DCD and EDR. It is also found that when the number of loops exceeds4, the phase distortion of the jamming signal decreases obviously, which makes the jamming system more likely to act as a radar indicator.